School culture's impact on school effectiveness and performance: comparison of teachers' and administrators' views - Özgenel, Mustafa; Dursun, İsmail Eray; Yıldız, Baran Barış; Mert, Pınar; Özgenel, Mustafa (Eğitim-Bir-Sen, 2021)
The aim of this study is to compare the effect of school culture on school effectiveness and performance according to the opinions of teachers and administrators. The sample of the study consists of 3468 teachers and 425 administrators working in Istanbul in the 2019-2020 academic year. Predictive survey model was used as the research model. The data were collected with the help of "School Culture Scale", "School Effectiveness Index" and "Performance Scale". The data were analyzed by correlation and regression analysis. While the task culture and support culture positively affected the performance of the teachers, respectively; bureaucratic culture and success culture do not affect teachers' performance. The support culture, task culture and success culture affect the school effectiveness the most, respectively. In addition, teachers' performance affects school effectiveness positively. While the support culture and task culture positively affect the performances of the managers, success culture and bureaucratic culture do not affect the performances of the administrators. While the support culture and bureaucratic culture affect school effectiveness the most, success and task culture do not. In addition, the performance of administrators has a positive effect on school effectiveness.

Bu çalışmanın amacı, okul kültürünün okul etkililiğine ve performansa olan etkisini öğretmen ve yönetici görüşlerine göre karşılaştırmaktır. Araştırmanın örneklemini 2019-2020 eğitim-öğretim yılında İstanbul İlinde görev yapan 3468 öğretmen ve 425 yönetici oluşturmaktadır. Araştırma modeli olarak yordayıcı tarama modeli kullanılmıştır. Veriler, “Okul Kültürü Ölçeği’’, “Okul Etkinliği Endeksi” ve ‘‘Performans Ölçeği’’ yardımıyla toplanmıştır. Veriler korelâsyon ve regresyon analizleri ile çözümlenmiştir. Bulgulara öğretmenlerin performansını sırayla en fazla görev kültürü ve destek kültürü olumlu yönde etkilerken; bürokratik kültür ve başarı kültürü öğretmenlerin performanslarını etkilememektedir. Okul etkililiğini sırasıyla en fazla destek kültürü, görev kültürü ve başarı kültürü etkilemektedir. Ayrıca öğretmenlerin performansı da okul etkililiğini olumlu yönde etkilemektedir. Yöneticilerin performanslarını sırayla en fazla destek kültürü ve görev kültürü olumlu yönde etkilerken, başarı kültürü ve bürokratik kültür yöneticilerin performanslarını etkilememektedir. Okul etkililiğini sırasıyla en fazla destek kültürü ve bürokratik kültür etkilerken, başarı ve görev kültürü etkilememektedir. Ayrıca yöneticilerin performansı da okul etkililiğini olumlu yönde etkilemektedir.
Okul Kültürünün Okul Etkililiğine ve Performansa Etkisi: Öğretmen ve Yönetici Görüşlerinin Karşılaştırılması
Keywords: School culture; School effectiveness; Teacher performance; Correlational survey model; Okul kültürü; Okul etkililiği; Öğretmen performansı; İlişkisel araştırma modeli